Critical thinking in foreign language teaching between argumentation and communicative collaboration (Altre Modernità, 2024)
National and international educational policies insist on the importance of critical thinking as a transversal competence of high civic and professional value, as well as academic. In particular, Universities have a role that is gradually assuming pedagogical depth on the European scene; consequently, they must take up new educational challenges, mainly related to how to train the skills that society requires. In this study we deal with the didactic difficulties of defining the goals of critical thinking training. To do so, we draw on the tradition of foreign language teaching related to argumentative and group collaboration skills. Over the years, these areas have calibrated many competency descriptors that intersect critical thinking and allow defining it in a concrete, visible and gradable way. This article offers tools for integrating critical thinking competence into foreign language teaching and support the competency training as an everyday practice at the university level.
Keywords: critical thinking; competence; argumentation; group work; foreign language descriptors